Predicting the effects of noise on Anuran spatial distribution: the case of Scinax nebulosus. Issue 4 (3rd July 2020) - Estrela, Matheus da N.; Simões, Cássio R. M. A.; Vieira, Gustavo H. C.; de Araújo, Carlos B.
ABSTRACT: Several animal groups depend on acoustic communication to survive and reproduce, bringing attention to the possible negative effects of increasing anthropogenic noise. We examined the role of acoustical communication on the small-scale distribution of Scinax nebulosus, and how this distribution is affected by acoustic noise. We performed playback experiments to estimate theoretical male-male distances and compared them to measured male-male distances. If sound does, in fact, dictate chorus spatial structure, our models should successfully predict frog's small-scale distribution in the field. By definition, communication should prompt a behavioral response, and playback experiments were designed to determine the intensity of a courtship call necessary to prompt the emission of territorial calls by males (call shift threshold – CST). If noise alters CST, our models should be able to predict its effect on small-scale distribution. Our results showed a positive correlation between experimental and theoretical distances, indicating that our theoretical model is capable of predicting male-male distances. Noise levels altered CST, suggesting that small-scale frog distribution is in fact affected by noise. Our results support the view that anuran vocalizations have a central role in their spatial structuring, and also that noise can interfere with small-scale distribution, causing aggregations to become denser.